2020
DOI: 10.31234/osf.io/dy92g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network Approach to Work Addiction: A Cross-Cultural Study

Abstract: The network approach to psychopathology (formalized as the network theory of mental disorders) conceptualizes mental disorders as dynamic systems consisting of symptoms which are in direct causal relationships with each other. The core rationale for the utility of the network approach is a belief that treatment and prevention programs would be more effective if targets of intervention were certain symptoms or direct causal relationships between pairs of symptoms rather than mental disorders as syndromes. As su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The engagement cluster showed stronger connection with the cluster including salience, mood modification, and withdrawal than with the cluster including tolerance, relapse, conflict, and problems. This disproportion in number and strength of the edges between the two pairs of clusters provides additional supports for the assumption that the two clusters represent groups of more and less pathological symptoms of work addiction (Bereznowski et al, 2021; see also Charlton & Danforth, 2007).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The engagement cluster showed stronger connection with the cluster including salience, mood modification, and withdrawal than with the cluster including tolerance, relapse, conflict, and problems. This disproportion in number and strength of the edges between the two pairs of clusters provides additional supports for the assumption that the two clusters represent groups of more and less pathological symptoms of work addiction (Bereznowski et al, 2021; see also Charlton & Danforth, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…A previous study showed that the pattern of direct relationships between symptoms of work addiction was almost identical for individuals of diverse cultural and sociodemographic backgrounds (Bereznowski et al, 2021). In each of the four networks, the most central symptom was relapse, and the least central symptom was mood modification.…”
Section: The Network Approach To Work Addictionmentioning
confidence: 86%
See 2 more Smart Citations
“…Also, studies based on clinical samples and epidemiological surveys, including other psychopathologies and studies investigating potential sex differences in networks, are highly warranted. These should include replication of the current study on study addiction conceptualized as an early form of work addiction (Atroszko et al, 2015(Atroszko et al, , 2016 Bereznowski, P., Atroszko, P. A., & Konarski, R. (2021). Network approach to work addiction: A crosscultural study showed a high replicability of networks across samples from different countries C2 = 150 001-300 000 NOK, C3 = 300 001-450 000 NOK, C4 = 450 001-600 000 NOK, C5 = 600 001-750 000 NOK, C6 = 750 001-900 000 NOK, C7 = 900 001-1 050 000 NOK, C8 = 1 050 001-1 200 000 NOK, C9 = 1 200 001-1 350 000 NOK, C10 = 1 350 001-1 500 000 NOK, C11 = 1 500 001 or more.…”
Section: Conclusion and Future Studies Directionsmentioning
confidence: 89%